R-loop disruption triggers irreversible topoisomerase 1–DNA cleavage complex formation during AID-dependent IgH gene diversification - Maki Kobayashi; Xi Chen; Tasuku Honjo (Proceedings of the National Academy of Sciences, 2026)
Class switch recombination (CSR) and somatic hypermutation are essential mechanisms of effective antibody production, dependent on the enzyme activation-induced cytidine deaminase (AID). Since AID lacks the intrinsic ability to cleave DNA, topoisomerase 1 (TOP1) has been hypothesized to mediate AID- and transcription-dependent DNA cleavage. However, the molecular mechanism underlying the formation of an irreversible TOP1–DNA cleavage complex (TOP1-CC) following cytidine to uridine (C-to-U) editing by AID remains undefined. To unveil this mechanism, we tested antisense oligonucleotides (ASOs) targeting noncoding germline transcripts (GLTs) that form R-loops across DNA cleavage sites during CSR. These studies revealed that the anti-GLT-ASOs increased DNA cleavage frequency, concomitant with a decrease in R-loops. Mechanistically, ASO-mediated R-loop disruption led to increased TOP1-CC formation specifically within the GLT region during CSR. Furthermore, an in vitro transcription assay demonstrated that RNase H-mediated R-loop degradation enhanced positive supercoiling and double-strand breaks in the presence of TOP1, even in the absence of AID. Moreover, knockout of Tyrosyl-DNA phosphodiesterase 1 ( Tdp1 ), a canonical TOP1-CC processing enzyme, revealed that TDP1 suppresses CSR, indicating that accumulated TOP1-CCs in Tdp1 knockout cells serve as substrates for CSR through an alternative TOP1-CC processing pathway. Collectively, these results suggest the R-loop destabilization as a critical, hitherto unrecognized intermediary step linking C-to-U editing to TOP1-CC formation. AID-mediated C-to-U editing within R-loops introduces a G:U wobble base pair, which we hypothesize renders R-loops unstable and sensitive to nuclear RNases, leading to R-loop disruption; this disruption consequently induces the TOP1-CCs and results in CSR, as confirmed in this study.